Vaccination Status and Socio-demographic Study of Laboratory Confirmed Measles Cases in Upazilla Hospitals of Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2020)
Background: Though Bangladesh has done well to reduce the measles cases and measles related deaths through an effective vaccination programme, measles cases are still found in a good number in hospitals. The objectives of our study was to find out the vaccination status of laboratory confirmed measles patients and also to see the socio-demographic status of those patients.Methodology: This is a descriptive cross-sectional study conducted in five Upazilla Health Complexes (UHC) of Gazipur district during a period of one year from 01/01/2017 to 31/12/ 2017. The Upazillas included were Gazipur Sadar, Kaliganj, Kaliakair, Sreepur and Tongi. The suspected measles patients were admitted after taking history and clinical examination and confirmed by doing specific laboratory investigation. Measles vaccination status and sociodemographic status of the these confirmed cases were analysed by using SPSS version 21.Results: Blood samples were sent from 93 patients who were admitted during the study period after observing the diagnostic criteria of measles. Out of them 45 patients were confirmed as measles and they are included in the study. Among the laboratory confirmed measles, 28 cases (62.22%) were males and 17 (37.78%) cases were females, ratio of male and female was 1.6:1. The maximum number of patients (62.22%) were in the age group of 9 months to 4 years. Maximum patients came from low socioeconomic condition with a monthly income of 10,000- 15,000 taka. About maternal education, 26 mothers (57.78%) were uneducated, 12(26.67%) below primary and 7(15.55%) up or above primary level. Among the total patients, 27(60%) patients came with pneumonia, 16(35.56%) patients with both pneumonia and diarrhoea and 2(4.44%) patients only with diarrhoea. We found 32 patients (71.11%) received no MCV(Measles containing vaccine) , 11 patients (24.44%) with one MCV and 2 patients (4.44%) received two MCVs. There we found several causes of dropout of measles vaccine. Lack of awareness regarding one vaccine was the most common cause (42.22%) and then ignorance about two measles vaccine (28.89) followed by migration (17.78%) and parental occupation (11.11%). History of contact with measles patients were found in 24.44% cases , no history in 26.67% cases and in 48.89% cases the history of contact is unknown.J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 86-90